The growth rate of hydroponic lettuce at various nutrient compositions from liquid synthetic, solid synthetic, and liquid organic fertilizers - Khodijah, Nyayu Siti; Santi, Ratna; Kusmiadi, Riwan; Asriani, Euis (Anjoro: International Journal of Agriculture and Business, 2021)
The hydroponic system of lettuce cultivation has become popular in the new normal era after the Covid 19 pandemic. So that the efficiency of input and the ease of supplying nutrients in hydroponic farming deserves to be a concern. Hydroponics commonly uses synthetic fertilizers that are completely available and sold commercially. Efforts are needed to make media choices by utilizing easier and cheaper resources, among others by making various alternative nutrient source compositions from widely available, cheap, and commonly used synthetic fertilizers such as NPK and Gandasil. Another option that also needs to be tested for the efficiency of its utilization is the use of liquid organic fertilizers from chicken feather waste. Calculation of the growth rate of lettuce grown on various nutrient compositions of liquid organic and synthetic fertilizers was carried out. The types of fertilizer composition tested were P1= AB-mix (control) 50 ml in 10 liters of water, P2= NPK 10 g + Gandasil 5 g in 10 liters of water, P3= AB-mix 25 ml + 5 g NPK + 2.5 g Gandasil in 10 liters of water, P4= AB-mix 25 ml + 400 ml chicken feather LOF in 10 liters of water, and P5= 5 g NPK + 2.5 g Gandasil + 400 ml chicken feather LOF in 10 liters of water. The results showed that the highest growth rate of lettuce was obtained in the P4 composition, with the best results for Net assimilation rate (NAR), total wet biomass production per plant, ratio of wet weight of shoot: wet weight roots, relative plant height growth rate, relative leaf number growth rate, and relative plant growth rate.